Faktor Keamanan Informasi dan Strategi Implementasi dalam Meningkatkan Adopsi E-Government di Sektor Publik Negara Berkembang: Tinjauan Literatur - Febrianty, Devi; Hilman, Muhammad; Yazid, Setiadi (The Indonesian Journal of Computer Science, 2024)
The development of e-government is increasingly prioritized in developing countries as part of digital transformation efforts to improve the quality of public services. However, challenges such as low adoption rates, public trust issues, and weak information security persist. This research aims to comprehensively identify information security factors influencing e-government adoption in developing countries and propose implementation strategies. The approach used is a combination of systematic literature review and snowballing technique. We categorized security factors using the Technology, Organization, and Environment (TOE) framework to aid analysis and strategy formulation. Findings show that non-technical factors, particularly organizational and environmental aspects (41% each), dominate over technical factors (18%). These results highlight the importance of strengthening security policies, risk management, and data protection regulations by the government, as well as efforts to improve public perception of information security. This research provides theoretical contributions through a TOE-based framework and practical strategies to increase e-government adoption.